Բարբառային, ժողովրդախոսակցական բառաշերտերը Նորայր Ադալյանի ստեղծագործություններում - Վիրաբյան, Ռուզան
Vocabulary according to its stylistic and expressive means is of literary and non-literary (with its sub-layers: dialects and slangs). Slangs are the words which are related to the culture, customs, every day life, double complexities, nature-related words, interjections, especially in the case of locutions and word combinations. The slangs belong to that part of the language which is not active and are out of literary language norms and are not applicable in functional styles, such as scientific, official etc. Thus, Norayr Adalyan’s works are rich with peculiar vocabulary, which are expressed in slangs and dialects. The skillful usage of words on behalf of the author contributes to the language development and richness of vocabulary, as well as introduction of new words. Norayr Adalyan’s language is rich an author’s specific words which, apart from complementing the dramatic literary creations of the author, and adding freshness to his style, also enrich the vocabulary of the Armenian language. Классифицируя с точки зрения стилистической и эмоциональновыразительной окраски словарный запас делится на лексические пласты: литературный и нелитературный (с диалектными и разговорными подгруппами слов). В литературный лексический пласт входят те слова, которые используются в пределах требований норм и применения литературного языка. Основную часть разговорного лексического пласта составляют слова и выражения, обозначающие быт, бытописание,традиции народа, повторы слов, звукоподражательные слова, междометия и в особенности фразеологизмы и словосочетания, имеющие значение фразеологического оборота. Диалектизмы стоят за пределами литературного языка и не принадлежат к активному словарному запасу, следовательно, не используются в официалььно-деловом и научном стилях. Таким образом, произведения Норайра Адаляна богаты своеобразным словарным запасом, который отражен в разговорном и диалектном лексических слоях. Искусное применение писателем речи способствует развитию языка и обогащению словарного запаса.
Keywords: Լեզվաբանություն; Բառապաշար